Carbon Governance Arrangements and the Nation‐State: The Reconfiguration of Public Authority in Developing Countries. (13th December 2017) - Hickmann, Thomas; Fuhr, Harald; Höhne, Chris; Lederer, Markus; Stehle, Fee
Summary: Several scholars concerned with global policy‐making have recently pointed to a reconfiguration of authority in the area of climate politics. They have shown that various new carbon governance arrangements have emerged, which operate simultaneously at different governmental levels. However, despite the numerous descriptions and mapping exercises of these governance arrangements, we have little systematic knowledge on their workings within national jurisdictions, let alone about their impact on public‐administrative systems in developing countries. Therefore, this article opens the "black box" of the nation‐state and explores how and to what extent two different arrangements, that is, Transnational City Networks and Reducing Emissions from Deforestation and Forest Degradation, generate changes in the distribution of public authority in nation‐states and their administrations. Building upon conceptual assumptions that the former is likely to lead to more decentralized, and the latter to more centralized policy‐making, we provide insights from case studies in Indonesia, South Africa, Brazil, and India. In a nutshell, our analysis underscores that Transnational City Networks strengthen climate‐related actions taken by cities without ultimately decentralizing climate policy‐making. On the other hand, Reducing Emissions from Deforestation and Forest Degradation tends to reinforce the competencies of central governments, but apparently does not generate a recentralization of the forestry sector at large.